Strengthening Student Concepts: Problem Ethnomatmatics Based Learning (PEBL) Singosari Kingdom Historical Site Viewed from Learning Styles in the Middle School Curriculum - Arian Sah, retno wahyu; Effendi, Mohammad Mahfud; Darmayanti, Rani; In'am, Akhsanul (IndoMath: Indonesia Mathematics Education, 2022)
Ethnographic problem-based learning (PEBL) motivates students to apply what they already understand and encourages them to absorb new knowledge. They introduce cultural questions to help integrate mathematics into everyday life to connect the essence and deepen understanding of mathematics. This study used a sample of eighth grade students of MTs Unggulan Singa Putih, Pasuruan, who were students from several public and private schools, and from Madrasah Tsanawiah who developed the PEBL model to strengthen the mathematical concepts of students from different learning styles. This study uses the Plomp research and development method (a. Initial evaluation, b. Design stage, c. Realization/development stage, d. Testing, evaluation, review and e. Implementation). The data technique uses literature study, observation, tests and interviews. Data is analyzed by organizing and subtracting, displaying, summarizing and verifying. This research identifies theoretical foundations and identifies models, identifies and evaluates PBL models and validates media experts, research experts and social mathematicians. The mathematical mathematical model is more effective with the combination of the PEBL model. The PEBL model was developed to improve and optimize the concepts of mathematics learning in geometry